2021
DOI: 10.1080/23802359.2021.1976686
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Ixodes vespertilionis (Acari: Ixodidae)

Abstract: Ixodes vespertilionis is a tick parasitizing on the bodies of bats. In our study, the complete mitogenome of I. vespertilionis was determined by using Illumina sequencing technology. The mitogenome was 14,559 bp in size and was predicted to encode 37 genes including 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and one control region. The gene order of the mitogenome is identical to Argasidae and non-Australasian Prostriata. The phylogenetic analysis by the Maximum-likelihood method re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…rufipes , Rhipicephalus microplus , and many soft tick mitogenomes [ 37 , 38 , 62 , 77 , 78 , 79 , 80 , 81 ]. Although Lu et al reported that no sequence identical to the Tick-Box consensus motif was present in I. vespertilionis mitogenome [ 82 ], we successfully found the motif within trnL1 (5′-TTGTATCAAATTTAGAA-3′) and downstream of ND1 (5′-TTGTATCCTTTT G AGAA-3′) on the light chain.…”
Section: Resultsmentioning
confidence: 82%
“…rufipes , Rhipicephalus microplus , and many soft tick mitogenomes [ 37 , 38 , 62 , 77 , 78 , 79 , 80 , 81 ]. Although Lu et al reported that no sequence identical to the Tick-Box consensus motif was present in I. vespertilionis mitogenome [ 82 ], we successfully found the motif within trnL1 (5′-TTGTATCAAATTTAGAA-3′) and downstream of ND1 (5′-TTGTATCCTTTT G AGAA-3′) on the light chain.…”
Section: Resultsmentioning
confidence: 82%
“…Adult samples of H. yeni were collected in March 2021 from High Li Gong Shan in the Nujiang Lisu Autonomous Prefecture of the Chinese Yunnan Province (26°34′N, 98°48′E) ( n = 2, female; n = 1, male). Professor Chunhong Du examined the species' morphological identification using the essential diagnostic features ( 13 ). After collection, one adult female specimen was used for DNA extraction, and the remainder of the ticks were held as voucher specimens.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were maintained at −80°C and preserved in 95% alcohol before being utilized for DNA extraction. Single tick genomic DNA was extracted using DNAzol (Life Technologies, USA) following the manufacturer's instructions and stored for further processing ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire DNA was extracted using the standard CTAB technique, for storage at −20 °C before use (Lu et al. 2021 ). The mitochondrial genome was sequenced on the Illumina NovaSeq platform (Shanghai Personal Biotechnology Co, Ltd) which was assembled using A5-miseq software (Coil et al.…”
mentioning
confidence: 99%